FRAME Study: The Foundation Effect of Building Bone With 1 Year of Romosozumab Leads to Continued Lower Fracture Risk After Transition to Denosumab. (17th May 2018) - Cosman, Felicia; Crittenden, Daria B; Ferrari, Serge; Khan, Aliya; Lane, Nancy E; Lippuner, Kurt; Matsumoto, Toshio; Milmont, Cassandra E; Libanati, Cesar; Grauer, Andreas
ABSTRACT: Romosozumab is a bone‐forming agent with a dual effect of increasing bone formation and decreasing bone resorption. In FRActure study in postmenopausal woMen with ostEoporosis (FRAME), postmenopausal women with osteoporosis received romosozumab 210 mg s.c. or placebo once monthly for 12 months, followed by denosumab 60 mg s.c. once every 6 months in both groups for 12 months. One year of romosozumab increased spine and hip BMD by 13% and 7%, respectively, and reduced vertebral and clinical fractures with persistent fracture risk reduction upon transition to denosumab over 24 months. Here, we further characterize the BMD gains with romosozumab by quantifying the percentages of patients who responded at varying magnitudes; report the mean T ‐score changes from baseline over the 2‐year study and contrast these results with the long‐term BMD gains seen with denosumab during Fracture REduction Evaluation of Denosumab in Osteoporosis every 6 Months (FREEDOM) and its Extension studies; and assess fracture incidence rates in year 2, when all patients received denosumab. Among 7180 patients ( n  = 3591 placebo, n  = 3589 romosozumab), most romosozumab‐treated patients experienced ≥3% gains in BMD from baseline at month 12 (spine, 96%; hip, 78%) compared with placebo (spine, 22%; hip, 16%). For romosozumab patients, mean absolute T ‐score increases at the spine and hip were 0.88 and 0.32, respectively, at 12 months (placebo: 0.03 and 0.01) and 1.11 and 0.45 at 24 months (placebo‐to‐denosumab: 0.38 and 0.17), with the 2‐year gains approximating the effect of 7 years of continuous denosumab administration. Patients receiving romosozumab versus placebo in year 1 had significantly fewer vertebral fractures in year 2 (81% relative reduction; p  < 0.001), with fewer fractures consistently observed across other fracture categories. The data support the clinical benefit of rebuilding the skeletal foundation with romosozumab before transitioning to antiresorptive therapy. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.